Evolution of neurovirulent Zika virus - Screaton, G; Mongkolsapaya, J (American Association for the Advancement of Science, 2017)
In 2015, Zika virus (ZIKV) became headline news after its association with fetal microcephaly (severely reduced head circumference) in Brazil and was declared a public health emergency by the World Health Organization (WHO) (1). However, ZIKV was not new, it was first isolated from the Zika forest, Uganda in 1947 (2). ZIKV incited little interest compared to other flaviviruses, such as dengue virus (DENV), as it was not thought to cause severe disease. ZIKV infections were largely sporadic, and symptoms were usually mild and flu-like, with self-limiting fever, rash, and conjunctivitis. Around 80% of cases were asymptomatic, and epidemic activity had not been described (3). In 2007, large-scale explosive outbreaks of ZIKV infection were described in Micronesia, and the virus spread across the Pacific, reaching South America in 2015, where it rapidly spread through Brazil and neighboring countries (3–5). On page 933 of this issue, Yuan et al. (6) compared sequences of contemporary ZIKV strains with ancestral ZIKV isolates and describe a mutation that increases the neurovirulence of contemporary strains, which they propose underscores the increased pathogenicity of recent outbreaks.